Impact of emotional intelligence training on modifying HIV risk perception of road safety personnel in Imo State, Nigeria (2011)
Road safety personnel in Nigeria are vulnerable to HTV/AIDS due to exposure to infected blood luring rescue operations. Studies have shown that they have low HIV risk perception. Regrettably, there is paucity of research targeting this group in Nigeria. This study investigated the effectiveness of Emotional Intelligence Training (EIT) on modifying HIV risk perception of Federal Road Safety Commission (FRSC) Personnel in Imo State, Nigeria. A pre-test-post-test, control group" experimental design with 2x2 factorial matrix was adopted for this study. Fifty male and fifty female with age range of 27 and 32 years (x =23.02; SD-3.7) were purposively drawn from two units of Imo Sector Command. HIV Risk Perception Questionnaire (r=0.84) was the outcome measure. Analysis of Covariance (ANCOVA) and t-test were the statistical methods adopted. Two null hypotheses were tested at 0.05 alpha level. The results revealed a significant treatment effect in comparison with the control Group [F (1, 95) =5.21, P<0.05). Gender did not significantly influence treatment outcomes. The potency of EIT in this study has implications for Psychologists, HCT Service Providers and Health Educators.